Robust equity portfolio management + website : formulations, implementations, and properties using MATLAB /: formulations, implementations, and properties using MATLAB. (2015) - (Associate professor), Kim, Woo Chang; Kim, Jang-Ho; Fabozzi, Frank J
No abstract available